Multiple-Scattering $T$-Matrix Simulations for Nanophotonics: Symmetries and Periodic Lattices (Communications in Computational Physics, 2021)
The multiple scattering method T-matrix (MSTMM) can be used to solve theelectromagnetic response of systems consisting of many compact scatterers, retaininga good level of accuracy while using relatively few degrees of freedom, largely surpassing other methods in the number of scatterers it can deal with. Here we extendthe method to infinite periodic structures using Ewald-type lattice summation, andwe exploit the possible symmetries of the structure to further improve its efficiency,so that systems containing tens of thousands of particles can be studied with relativeease. We release a modern implementation of the method, including the theoreticalimprovements presented here, under GNU General Public Licence.
Keywords: T-matrix; multiple scattering; lattice modes; symmetry-adapted basis; metamaterials; Ewald summation.